Pengembangan Produk Unggulan Daerah Berorientasi Ekspor Pada Industri Kerajinan Batu Alam Nusa Tenggara Timur - Amheka, Adrianus; Ga, Jonri Lomi; Noach, Robert M. (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Regional superior products in NTT Province are currently the main pillars of the people's economy. Through the development program of superior products of export-oriented regions in the natural stone handicraft industry in UD Pesona Batu Alam, it is able to increase productivity, turnover and other assets. The support of Kupang State Polytechnic through the improvement of innovation-based mechanization on the types and kinds of production needed by the community through craftsmen in UD. Pesona Batu Alam is very necessary. Measured activities include the development of rock type designs through a variety of forms to attract tastes of domestic and foreign customers. The implementation methods that are carried out include the manufacture and application of cutting tool technology and portable stone grading screw systems to be part of the innovation targeted in this service program. The characteristics of the tool are designed in accordance with the conditions of natural stone and NTT Province's distinctive limestone products. The results of this service program are able to improve the quality of products, including the use of by-products in addition to being able to stimulate sales and marketing between islands and between neighboring countries.